2021
DOI: 10.1002/fsn3.2475
|View full text |Cite
|
Sign up to set email alerts
|

The effects of ginseng on the metabolic syndrome: An updated review

Abstract: Metabolic syndrome or syndrome X is the name given to the collection of clinical conditions including overweight, high blood pressure, high blood glucose (or type 2 diabetes mellitus), and hyperlipidemia (Chen et al., 2017).Metabolic syndrome is the most important risk factor for atherosclerosis in response to chronic inflammation and vascular endothelial dysfunction. Metabolic syndrome increases the risk of cardiovascular diseases. Cardiovascular diseases are the main reasons for mortality around the world . … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 149 publications
0
14
0
Order By: Relevance
“…Panax ginseng has been shown to contain the Ginsenoside Rg1, which is able to promote browning, by inducing UCP1 expression and by modulating the transcription factor PRDM16 and PGC1α [ 25 , 26 ]. However, this modulation depends on Irisin, an adipomyokine, which promotes WAT browning, acting both in adipose and muscle tissue [ 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Panax ginseng has been shown to contain the Ginsenoside Rg1, which is able to promote browning, by inducing UCP1 expression and by modulating the transcription factor PRDM16 and PGC1α [ 25 , 26 ]. However, this modulation depends on Irisin, an adipomyokine, which promotes WAT browning, acting both in adipose and muscle tissue [ 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Rather than extracting individual compounds to produce exercise supplements, such as caffeine [ 22 , 23 ], capsaicin [ 24 , 25 ], and taurine [ 26 ], ginseng is extracted and utilized as a whole. As it contains various active compounds (ginsenosides), it delivers multiple benefits such as antioxidant [ 27 ], anti-obesity [ 28 ], and anti-fatigue [ 29 ], unlike the exercise supplements that exhibit only a single effect [ 30 ]. Recently, various studies have been conducted on the effects of exercise and complex intake on angiogenesis [ 31 , 32 ], immune response [ 33 ], antioxidant [ 34 ], and anti-fatigue [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Korean red ginseng (Araliaceae; Panax ginseng C.A.Mey) has been used in folklore medicine for 2000 years and is currently being investigated for a variety of conditions including metabolic syndrome ( Aminifard et al, 2021 ), inflammatory bowel disease ( Kang et al, 2021 ) and diabetes ( Liu et al, 2021 ). Studies have shown that Korean red ginseng has otoprotective activities including alleviation of cisplatin-induced ototoxicity in vitro and in vivo ( Im et al, 2010 ), attenuation of noise-induced hearing loss ( Mungan Durankaya et al, 2021 ) and amelioration of cochlear damage ( Tian et al, 2013 ) and vestibular dysfunction ( Tian et al, 2014 ).…”
Section: Other Herbal Medicines For the Treatment Of Tinnitusmentioning
confidence: 99%